Sejarah Gerakan Sosial Islam Syekh Ahmad Rifa’i di Indonesia Adab Ke-19 - Erwin Padli; Zaenudin Amrulloh (JURNAL PENELITIAN KEISLAMAN, 2022)
The displacement of the royal elite from political affairs to be replaced by the colonial government automatically meant the loss of royal patronage of its people in the 19th century. Therefore it is only natural that the people then seek protection from charismatic figures outside the royal elite, among them are kyai and clerics, one of whom is Sheikh Ahmad Rifa'i. To explore the history data, researchers used a literature review approach. This movement started as a purely religious movement, but due to the increasing number of members, it is considered as a movement that is against the government. In its journey as a social-religious movement, the movement driven by Sheikh Ahmad Rifa'i received various upheavals, both from indigenous figures to the Dutch colonial government. However, in general, this movement was considered to be against the government, so it was isolated in the Kalisalak area